Postoperative analgesic effect of intravenous coinjection of lidocaine and dexmedetomidine in gynaecological surgery: a systematic review and meta-analysis - Dan Xie; Wen Wen; Fangjun Wang; Hongqiong Li (BMJ Open)
Objectives Hysterectomy or myomectomy is a common gynaecological procedure that results in moderate to severe acute postoperative pain, which can cause many adverse effects. This study aimed to compare the postoperative analgesic efficacy, opioid consumption, quality of postoperative recovery (QOR) and adverse reactions of intravenous coinjection of lidocaine and dexmedetomidine versus lidocaine or dexmedetomidine alone in gynaecological surgery.Design Systematic review and meta-analysis was performed.Data sources The PubMed, Embase, Cochrane Library and Web of Science databases were used to access the articles. Electronic databases were searched for eligible studies published before 1 May 2024.Eligibility criteria All randomised controlled trials (RCTs) were included in the final analysis in which the intraoperative intervention group received intravenous coinjection of lidocaine and dexmedetomidine, and the control group received intravenous injection of lidocaine or dexmedetomidine alone in gynaecologic procedures.Data extraction and synthesis Study retrieval, literature screening, data extraction and risk of bias assessment were performed independently by two reviewers. The quality of included studies was assessed by the Cochrane Collaboration Risk of Bias (ROB V.2.0). Data were expressed as standardised mean difference, weighted mean difference or relative risk with 95% CI. Review Manager V.5.4 was used for data analysis.Results A total of five RCTs were included, involving 672 patients, of which 224 patients received coinjection of lidocaine and dexmedetomidine. The results revealed that coinjection of lidocaine and dexmedetomidine was superior to individual lidocaine in the visual analogue scale (VAS) scores at 1 hour (MD=−0.90, 95% CI (−1.11 to –0.69), p<0.001), 2 hours (MD=−0.99, 95% CI (−1.19 to –0.80), p<0.001), 4 hours (MD=−1.20, 95% CI (−1.75 to –0.66), p<0.001), 6 hours (MD=−1.09, 95% CI (−1.48 to –0.70), p<0.001), 8 hours (MD=−1.22, 95% CI (−1.61 to –0.83), p<0.001) and 12 hours (MD=−0.76, 95% CI (−1.35 to –0.17), p=0.o1) after surgery. Compared with the dexmedetomidine group, the lidocaine+dexmedetomidine group had low VAS scores at 1 hour (MD=−0.60, 95% CI (−0.83 to –0.37), p<0.001), 2 hours (MD=−0.70, 95% CI (−0.87 to –0.53), p<0.001), 6 hours (MD=−0.79, 95% CI (−0.98 to –0.59), p<0.001), 8 hours (MD=−0.77, 95% CI (−1.25 to –0.28), p=0.002) and 12 hours (MD=−0.56, 95% CI (−1.00 to –0.11), p=0.01) after surgery. Coinjection of lidocaine and dexmedetomidine resulted in significantly lower postoperative opioid consumption, postoperative nausea and vomiting and bradycardia than lidocaine alone (all p<0.05). Compared with the dexmedetomidine group, the lidocaine+dexmedetomidine group shortened the time to intestinal transit resumption (p=0.003). Coinjection of lidocaine and dexmedetomidine reduced intraoperative opioid consumption and increased QOR scores compared with lidocaine and dexmedetomidine alone (all p<0.05).Conclusion Lidocaine combined with dexmedetomidine had superior analgesic efficacy and safety. However, due to the limitation in the number of available studies, more large-scale, prospective RCTs are needed for further investigation.PROSPERO registration numberCRD42023384018.